The Role of Madrasahs in Instilling Religious Moderation for Students at MAS YPI Batang Kuis - Yusuf, Muhammad; Ibrahim Hasibuan, Ahmad; Hasanah Lubis, Leli; Sadikin Ritonga, Ali; Azhar, Azhar (LPPPIPublishing, 2025)
This study discusses the role of the Private Madrasah Aliyah (MAS) YPI Batang Kuis in instilling religious moderation in students as an effort to form a tolerant, inclusive, and balanced character in understanding Islamic teachings. The approach used in this study is qualitative with a case study method, where data is collected through interviews, observations, and documentation. The results of the study indicate that religious moderation in this madrasa is implemented through the integration of Wasathiyah Islamic values ??in the curriculum, extracurricular activities, and the role models of teachers and educators. Programs such as interfaith discussions, Islamic studies, and social actions are effective means of building moderate attitudes among students. This study also reveals several challenges in the implementation of religious moderation, such as the influence of the social environment which is still exclusively oriented and the limited teaching materials that are in accordance with the principles of moderation. Therefore, synergy is needed between madrasas, the government, and the community in strengthening religious moderation education through increasing teacher capacity, developing a more contextual curriculum, and providing adequate learning resources. With these steps, MAS YPI Batang Kuis is expected to continue to contribute to forming a generation that has an inclusive religious understanding and is able to live side by side harmoniously in a pluralistic society.